Secondary Students’ Experiences in Learning Speaking through Digital Storytelling Project - Uswatun Hasanah; Kusrin Kusrin; Elih Sutisna Yanto (Jurnal Ilmiah Wahana Pendidikan, 2021)
The present interview study reports on two secondary students of the implementation of Digital Storytelling (DST) in learning speaking. The research question was: what is students’ experiences in learning to speak through DST? The research was conducted in the Secondary High School in Cikampek-Karawang in which two students with different levels of English proficiency participated in this study. The data of the research were collected from open-ended questionnaires and interviews. The result shows that there is an improvement in the students’ speaking skills after the creation of digital storytelling and students had positive experiences of digital storytelling. Furthermore, the author suggests that DST is beneficial for learning.